2020
DOI: 10.18632/aging.103522
|View full text |Cite
|
Sign up to set email alerts
|

Controlled attenuation parameter value-based diagnostic algorithm improves the accuracy of liver stiffness measurement in chronic hepatitis B patients

Abstract: Liver stiffness measurement (LSM) frequently overestimates the severity of liver fibrosis because of steatosis. However, the impact of the controlled attenuation parameter (CAP) on liver stiffness cutoff values remains unknown; CAP was used to quantify and diagnose the severity of hepatic steatosis. The study was conducted to determine the effect of CAP on liver stiffness cutoff values in chronic hepatitis B (CHB) patients. A retrospective cross-sectional study was performed in liver biopsy-proven CHB patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[12] However, there are concerns regarding the accuracy of CAP and LSM in evaluating steatosis and brosis in those patients. [13] Studies based on histological changes in steatosis and brosis are required to con rm the conclusion and elucidate the mechanisms drawn through noninvasive tests.…”
Section: Introductionmentioning
confidence: 99%
“…[12] However, there are concerns regarding the accuracy of CAP and LSM in evaluating steatosis and brosis in those patients. [13] Studies based on histological changes in steatosis and brosis are required to con rm the conclusion and elucidate the mechanisms drawn through noninvasive tests.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, there are concerns regarding the accuracy of CAP and LSM in evaluating steatosis and fibrosis in those patients. 13 This study was conducted in compliance with the ethical principles of the Declaration of Helsinki and was approved by the ethics committee. Written informed consent was obtained from all patients before enrollment.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of CHB patients who did not meet antihepatitis B Virus (HBV) indication, conducted in Hong Kong, persistent severe hepatic steatosis defined by controlled attenuation parameter (CAP) was independently associated with fibrosis progression, evaluated by liver stiffness measurement (LSM) (odds ratio [OR] = 2.379, p = 0.01) 12 . However, there are concerns regarding the accuracy of CAP and LSM in evaluating steatosis and fibrosis in those patients 13 . Studies based on histological changes in steatosis and fibrosis are required to confirm the conclusion and elucidate the mechanisms drawn through noninvasive tests.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis confirmed that CAP can effectively evaluate hepatic steatosis in patients with autoimmune liver disease (AILD), regardless of the acute or chronic course ( 16 ). CAP can identify steatosis independently of intrahepatic inflammation (such as ALT elevation) ( 17 19 ). This paper includes multicentre research data with a relatively large sample size to analyse the impact of baseline hepatic steatosis on the biochemical response, development of liver fibrosis, and long-term clinical outcome of AIH patients by innovatively utilizing this easily accessible steatosis quantification.…”
Section: Introductionmentioning
confidence: 99%